Kooperatifleşme olgusu ve kooperatifleşme sorunları - Tülümen, İpek (Fen Bilimleri Enstitüsü, 1991)
1950 ' li yıllardan itibaren kırsal kesimden kentle re doğru yapılan göçler sonucu, büyük şehirlerde konut açığı meydana gelmiştir. 1980 'li yıllara kadar konut sorununu çözecek etkili bir önlem alınamamıştır. 1980 sonrası bütçe dışı kaynaklar oluşturularak konut üretimi arttırılmıştır. Tez çalışmasında kooperatif üniteleri bir anket çalışmasıyla incelenmiştir. Toplu konutun genel olarak tanımlanması, yapı kooperatifinin tanımı, örgütlenmesi, gelişimi, yapı kooperatifleri yapımında başarılı olunması için izlenen yollar, üretimde karşılaşılan sorunlar incelenmiştir. Kooperatif uygulamaları ile ilgili örnekler vere bilmek için İstanbul'da Halkalı Projesi ve Bakırköy civarındaki toplam 30 adet kooperatif incelenmiştir. İnceleme sonuçları değerlendirilmiş, uygulamadaki hatalar belirlenmiş, konut sorununun çözülebilmesi için alınması gereken önlemler tez çalışmasında yer almıştır.

Large number of people came from village to cities since 1950' s so the urban population increased five times as much. As a natural result of this increase in popula tion, we need new houses in the cities and new houses have had to be built in Urban areas. After 1970' s some municipalities of some cities formed projects. They aimed to give these areas to the cooperatives. Their sources were few so they used the re sources of the social security institutions such as the ministry of public works, the building land office and the National Insurance Cooperation. The first law number 2487 on Building of Housing Estates came in to force in 1981. The second law number 2985 on Building of Housing Estates and made it possible to obtain new financial re sources for the construction of housing Estates. After 1980, the housing fond had a positive effect on the houses and the problems and defects in the inita- tives for the construction of housing estates. A housing estate is an itiative for providing of housing or residence on a large scale, that is materiza- lized by public or private institutions such as partner ships for the construction of housing, estates, housing cooperatives and banks of housing, and that meet the housing needs of large number of families. The concept of housing estate can also be defined with a scale: i- Social reasons, ii- Economic reasons, iii- Planning reasons. Cooperatives help people to be owner of houses with their few sources. In order to be succesfull in the construction of building cooperatives, the followin requirements must be fulfilled. - To find building land. It is necessary to find cheap building land. - Designing service. - Organization, formation of partners. - Obtaining credits. vi - Construction. - Settlement of housing. The people who will live in the housing unit will be necessary equipment. The problems faced in the constivetion of housing cooperatives are as follows. 1- The problems faced in the obtaining of building land. 2- The problems that arise from teh formation of the members and organization. 3- The problems in financing and obtaining credits. 4- Inspection problems. 5- The problems that arise when housing estatues change possession. 6- The building design problems in the applicati ons when housing cooperatives are constructed. 7- The tax problems in the applications when housing cooperatives are constructed. 8- The settlement problem when the construction is finished. 9- The technological problems that arise during the application of housing cooperatives. 10- The constractor problem that arises in to application of housing cooperatives. 11- The problems with finding qualified personel. This part of thesis which covers the cooperatives development all over the world. For example, in England, in Sweden, in America, in Germany, in France, in Spain, in India, in Poland were examined cooperatives how to de velop. The development of cooperatives in Turkey after 1980 and before 1980 were examined. In the thesis, present condition number and cha racteristics of cooperatives with 30 units. The 30 housing cooperative units which were built consist of totaly 4700 flats. The number of flats with an area of 50-75 squarmeter is 1691. The number of flats whose area varies between 75 squaremeters and 100 vix squaremeters is 2254. She number of flats whose area more-,, then lOO square meter is 1251. In order to construct more housing units in Turkey the following measures must be taken. -Priority must be given to new tow> projects. -Land credits must be given. -Hew sources must be found for the housing fund. -To build social houses must be encouraged. The problem with the units build in the areas are similar, to the problems with the housing unit all over Turkeır. The results of cooperatives with 50 units are as follows. -The problem faced in the obtaining of cheap building land. 55% cooperative managers buy land before and 45% buy after cooperative organization. -People have to be confident for choose the cooperative. (50%). 30% for being an owner a house, 10% for living green and good environment, 105: for the building land's situation. -Although the purpose of the cooperatives to be owner a house for low-income groups, the member of cooperatives are trademan (45%), are official (20&), are workers (15%), are craftsman (10%), are doctors, engineers or lawyers etc. (10%) -The members of the cooperatives have to pay 25-30% rates of their montly income. -She manager of the cooperatives are very important for the members. Members are prefer well-known and succesful managers. -The result of high-prices the low- income group members can't pay monthly so they have to sell their shares so they can't be the owner of the houses. -The credits can use only 15-20% of the whole cost. The cost is growing but the credit is fixed. -The number of families who get credits from the housing fund are 67%. The number of those who did not get any credits in 13%. -The credits must be given at low interest even for the units with an area of 6I-8E m, Şut most of credits are given for the units with an area of 100-150 m.(32%) The rates of area of 80 m are 9%. -45% cooperatives are taken II million TL.,20% are 9,5 million TL.,I5% are 8 million TL. credit from housing fund. (for one person) -The managers of cooperatives are not pleased for taking credits conditions.50% prefer to take credit when the construction level is 20%, 30% prefer when they buy the building land. -Lots of cooperative units haven't any equipment like social buildings, schools, hospitals or markets in working distance unixs. The results and offers are as follows. The purpose of housing cooperatives have xo build houses for low and miadle income group members with good conditions and have to complete the units as quick as possible. -The members use their savings ups by buying a coopera tive house. -Building cooperatives remove the specuiaters and real estate developers who were only interested in making money between the members and cooperative management. -The goverment have to build small houses for using profitable the housing fund. -If they avoid from luxury houses, they can controll the land speculation so they can controll the construction cost as well. -Cooperative houses can prevend mass housing. -Experts have to work to be succesfull for the project. Experts have to contain'. architects, city planners and some engineers. -Housing fund's sources have to be increased. -Local administration can help to cooperatives for buying the building land. -Local administration can sell their small building land and can buy large building lands for cooperative units. -Goverment have to secure different paying conditions for low- income groups. -Cooperatives can't use credit from the housing fund easily. -Some private institutions must be encouraged to build houses and service tenements fbr their own employees. -Construction materials and- house project must be standart. -Industrial construction technology must be used.
Problems and complications faced in the cooperative houses
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1991
Keywords: Konut kooperatifleri; Kooperatifleşme; Toplu konutlar; Housing cooperatives; Cooperativize; Mass houses